Responsible Leadership Fuels Innovative Behavior: The Mediating Roles of Socially Responsible Human Resource Management and Organizational Pride - Dong, Wenli; Zhong, Lifeng (Frontiers in Psychology, 2021)
Leaders are under increasing pressure to inspire innovative endeavors in responsible ways. However, whether and how responsible leadership can fuel employee innovative behavior remains unknown. Therefore, drawing on social identity theory and social exchange theory, this study aims to investigate the psychological mechanisms underlying the responsible leadership-innovative behavior relationship. Multi-phase data were collected from 280 employees working in Chinese manufacturing firms to test the hypotheses using hierarchical regression analyses and the bootstrap method. The results reveal that responsible leadership is positively related to innovative behavior. Additionally, perceived socially responsible HRM and organizational pride separately and sequentially mediate the responsible leadership-innovative behavior relationship. This study empirically reveals the effectiveness of responsible leadership and sheds new light on the psychological processes through which it facilitates innovative behavior, revealing the generalizability of responsible leadership and innovative behavior in the Chinese context. Moreover, we respond to the call for incorporating leadership theory into HRM research and further advance the existing knowledge on both antecedents and outcomes of socially responsible HRM. For practical guidance, organizations are encouraged to foster innovation through investment in responsible management practices. Research limitations and implications are also discussed.